Continuous positive airway pressure and adverse cardiovascular events in obstructive sleep apnea: are participants of randomized trials representative of sleep clinic patients?. Issue 4 (5th November 2021) - Reynor, Ayesha; McArdle, Nigel; Shenoy, Bindiya; Dhaliwal, Satvinder S; Rea, Siobhan C; Walsh, Jennifer; Eastwood, Peter R; Maddison, Kathleen; Hillman, David R; Ling, Ivan; Keenan, Brendan T; Maislin, Greg; et al.
Abstract: Study Objectives: Randomized controlled trials (RCTs) have shown no reduction in adverse cardiovascular (CV) events in patients randomized to continuous positive airway pressure (CPAP) therapy for obstructive sleep apnea (OSA). This study examined whether randomized study populations were representative of OSA patients attending a sleep clinic. Methods: Sleep clinic patients were 3, 965 consecutive adults diagnosed with OSA by in-laboratory polysomnography from 2006 to 2010 at a tertiary hospital sleep clinic. Characteristics of these patients were compared with participants of five recent RCTs examining the effect of CPAP on adverse CV events in OSA. The percentage of patients with severe (apnea-hypopnea index, [AHI] ≥ 30 events/h) or any OSA (AHI ≥ 5 events/h) who met the eligibility criteria of each RCT was determined, and those criteria that excluded the most patients identified. Results: Compared to RCT participants, sleep clinic OSA patients were younger, sleepier, more likely to be female and less likely to have established CV disease. The percentage of patients with severe or any OSA who met the RCT eligibility criteria ranged from 1.2% to 20.9% and 0.8% to 21.9%, respectively. The eligibility criteria that excluded most patients were preexisting CV disease, symptoms of excessive sleepiness, nocturnal hypoxemia and co-morbidities. Conclusions: A minority of sleep clinic patients diagnosed with OSA meet the eligibility criteria of RCTs of CPAP on adverse CV events in OSA. OSA populations in these RCTs differ considerably from typical sleep clinic OSA patients. This suggests that the findings of such OSA treatment-related RCTs are not generalizable to sleep clinic OSA patients. Randomized Intervention with Continuous Positive Airway Pressure in CAD and OSA (RICCADSA) trial, https://clinicaltrials.gov/ct2/show/NCT00519597, ClinicalTrials.gov number, NCT00519597. Usefulness of Nasal Continuous Positive Airway Pressure (CPAP) Treatment in Patients with a First Ever Stroke and Sleep Apnea Syndrome, https://clinicaltrials.gov/ct2/show/NCT00202501, ClinicalTrials.gov number, NCT00202501. Effect of Continuous Positive Airway Pressure (CPAP) on Hypertension and Cardiovascular Morbidity-Mortality in Patients with Sleep Apnea and no Daytime Sleepiness, https://clinicaltrials.gov/ct2/show/NCT00127348, ClinicalTrials.gov number, NCT00127348. Continuous Positive Airway Pressure (CPAP) in Patients with Acute Coronary Syndrome and Obstructive Sleep Apnea (OSA) (ISAACC), https://clinicaltrials.gov/ct2/show/NCT01335087, ClinicalTrials.gov number, NCT01335087.